EKSISTENSI KETERWAKILAN PEREMPUAN DI BAWASLU KABUPATEN/KOTA PROVINSI RIAU PERIODE 2023-2028: THE EXISTENCE OF WOMEN'S REPRESENTATION IN THE REGENCY/CITY BAWASLU OF RIAU PROVINCE FOR THE PERIOD 2023-2028 - imelda sapitri; Muammar Alkadafi (Yayasan Lembaga Pendidikan Asas, 2023)
Abstract General election is a routine agenda in the democratization of Indonesia as an arena for selecting leaders. The success and failure of elections depend on the election organizers. The General Election Supervisory Agency (BAWASLU) is an election-organizing institution that oversees and even takes action against violations. Therefore, women's representation in this institution is very necessary to ensure the fulfillment of women's political rights. In order to realize a better democratic system in Indonesia, Women's representation is regulated in Law Number 7 of 2017 concerning General Elections, in Article 92, Section 11, which reads:The composition of the membership of Bawaslu, Provincial Bawaslu, Regency Bawaslu, and City Bawaslu pays attention to women's representation of at least 30% (thirty percent). Based on this law, the author conducts normative legal research with two problem formulations below: a. How is the existence of women's representation in the regency or city of Bawaslu in Riau Province for the period 2023–2028? b. What is the urgency of women as members of the Regency or City Bawaslu of Riau Province? After conducting research with the results, the selection process of the Regency/City Bawaslu has 4 stages (administrative selection stage, written and psychological selection stage, health and interview selection stage, and fit-and-proper test selection stage).After carrying out 4 selection stages, 7 female members were elected in 12 regencies or cities, with the following details: Indragiri Hilir has 1 female member, and Indragiri Hulu has 1 female member. Kuantan Singingi has 1 female member, Rokan Hilir has 2 female members, Dumai City has 1 female member, and Pekanbaru City has 1 female member, while 6 districts such as Bengkalis, Kampar, Meranti, Pelalawan, Rokan Hulu, and Siak have no female representation. And the urgency of women's representation as members of the regency or city of Bawaslu is: a. Implementation of women's political rights; b. Increasing partnerships with women's organizations; c. increasing participatory supervision; d. Women becoming role models for other women to take part in the selection of Bawaslu members in the regency or city in the future.